A new Neoleptophlebia Kluge, 1997 species from eastern China (Ephemeroptera: Leptophlebiidae) - Wang, Kai-Chen; Yang, Qing-Yi; Zhou, Chang-Fa (Zootaxa, 2023)
The genus Neoleptophlebia Kluge, 1997 includes five Asian species. Three of them were reported from northeastern Asia and two were found from Chinese Taiwan Island, leaving a huge geographic gap on the Chinese mainland. Here we find a new one, which is named N. uncinata Zhou sp. nov., from Nanjing municipality, eastern China. Via field collecting and indoor rearing, all life stages were obtained, and its nymphs are found living in small creeks (with a width less than 1 m) and shallow waters (with a depth less than 30 cm). Diagnostically, the imago of this new species has larger lateral penial appendages than its congeners, and its nymph has subequal broadened segments II and III of maxillary and labial palpi. Biogeographically, this species bridges two northern and southern groups of the genus.